1947
DOI: 10.1099/00221287-1-2-158
|View full text |Cite
|
Sign up to set email alerts
|

Production of Antifungal and Antibacterial Substances by Fungi; Preliminary Examination of 166 Strains of Fungi Imperfecti

Abstract: SUMMARY:One hundred and sixty-six strains of Fungi Imperfecti have been examined primarily for the production of antifungal substances, though antibacterial substances have also been sought in most cases.Antifungal substances were produced by several species of Aspergillus and Penicillium, Fusarium caeruleum, Metarrhizium glutinosum, Stachybotrys atra, Trichoderrna viride, Gliocladium catenulatum and Trichothecium roseum. Antibacterial substances were produced by species of Aspergillus, Fusarium, Penicillium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1949
1949
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…produced bacteriostatic substances against Bacterium coli, S. aureus, and Pseudomonas pyocyanea. Brian and Hemming (1947) reported that the culture filtrates of different species of Aspergillus displayed antibacterial activity against S. aureus and Salmonella typhi. Irobi et al (2000) worked on A. quadrilineatus isolated from moldy Acha, a common cereal grown among the plateau state of Nigeria.…”
Section: Antibacterial Properties Of Crude Extractsmentioning
confidence: 99%
“…produced bacteriostatic substances against Bacterium coli, S. aureus, and Pseudomonas pyocyanea. Brian and Hemming (1947) reported that the culture filtrates of different species of Aspergillus displayed antibacterial activity against S. aureus and Salmonella typhi. Irobi et al (2000) worked on A. quadrilineatus isolated from moldy Acha, a common cereal grown among the plateau state of Nigeria.…”
Section: Antibacterial Properties Of Crude Extractsmentioning
confidence: 99%
“…The presence of an antifungal compound in culture filtrates of Trichothecizlm roseurn was reported by Brian & Hemming (1947), and the substance, trichothecin, responsible for the antifungal activity was isolated and some of its chemical and biological properties described by Freeman & Morrison (1949 a, b), In addition to its antifungal action, trichothecin was reported by Hessayon (1951) to give well-marked stimulation of mycelial growth, at exceedingly small concentrations. Other metabolic products of the mould have been described by Robertson, Smithies & Tittensor (1949) and by Freeman, Morrison & Michael (1949).…”
mentioning
confidence: 99%
“…The basis for choosing the RP chromatography is the nature and type of the selected compound. Mycophenolate mofetil is a low molecular weight, ester pro-drug of mycophenolic acid (MPA) [8] and hence is a neutral molecule. Reversed phase chromatography is the first [33,34].…”
Section: Resultsmentioning
confidence: 99%